Comparative Genomic Analysis of Vibrio diabolicus and Six Taxonomic Synonyms: A First Look at the Distribution and Diversity of the Expanded Species - Turner, Jeffrey W.; Tallman, James J.; Macias, Amanda; Pinnell, Lee J.; Elledge, Nicole C.; Nasr Azadani, Danial; Nilsson, William B.; Paranjpye, Rohinee N.; Armbrust, E. V.; Strom, Mark S. (Frontiers in Microbiology, 2018)
Vibrio is a diverse genus of Gammaproteobacteria autochthonous to marine environments worldwide. V. diabolicus and V. antiquarius were originally isolated from deep-sea hydrothermal fields in the East Pacific Rise. These species are closely related to members of the Harveyi clade (e.g., V. alginolyticus and V. parahaemolyticus) that are commonly isolated from coastal systems. This study reports the discovery and draft genome sequence of a novel isolate (Vibrio sp. 939) cultured from Pacific oysters (Crassostrea gigas). Questions surrounding the identity of Vibrio sp. 939 motivated a genome-scale taxonomic analysis of the Harveyi clade. A 49-genome phylogeny based on 1,109 conserved coding sequences and a comparison of average nucleotide identity (ANI) values revealed a clear case of synonymy between Vibrio sp. 939, V. diabolicus Art-Gut C1 and CNCM I-1629, V. antiquarius EX25 and four V. alginolyticus strains (E0666, FF273, TS13 and V2). This discovery expands the V. diabolicus species and makes available six additional genomes for comparative genomic analyses. The distribution of the expanded species is thought to be global given the range of isolation sources (horse mackeral, seawater, sediment, dentex, oyster, artemia and polycheate) and origins (China, India, Greece, United States, East Pacific Rise and Chile). A subsequent comparative genomic analysis of this new eight-genome subclade revealed a high degree of individual genome plasticity and a large repertoire of genes related to virulence and defense. These findings represent a significant revision to the understanding of V. diabolicus and V. antiquarius as both have long been regarded as distinct species. This first look at the expanded V. diabolicus subclade suggests that the distribution and diversity of this species mirrors that of other Harveyi clade species, which are notable for their ubiquity and diversity.